2012
DOI: 10.1055/s-0032-1314957
|View full text |Cite
|
Sign up to set email alerts
|

Planungsgenauigkeit bei Open Wedge HTO

Abstract: The results are comparable to those of other publications. However, taking into account the required accuracy of the drawn plan combined with the surgical precedure, it is not possible to achieve results within the desired tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Alignment was determined with the long-leg fully weight-bearing AP radiograph. The deformity analysis was performed according to Paley et al 29 and planning of the osteotomy was performed according to Miniaci et al 30 Because of well-known inaccuracy using the drawing method, 31 we used the digital technique which was described by Elson et al 32 If the correct angle was more than 15 degrees, according to the preoperative plan, the patient was excluded from this study. Before surgery, we used CT images to design and fabricate threedimensional (3D)-printed patient-specific instrument (PSI) guides for clinical use.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…Alignment was determined with the long-leg fully weight-bearing AP radiograph. The deformity analysis was performed according to Paley et al 29 and planning of the osteotomy was performed according to Miniaci et al 30 Because of well-known inaccuracy using the drawing method, 31 we used the digital technique which was described by Elson et al 32 If the correct angle was more than 15 degrees, according to the preoperative plan, the patient was excluded from this study. Before surgery, we used CT images to design and fabricate threedimensional (3D)-printed patient-specific instrument (PSI) guides for clinical use.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…Limited accuracy in osteotomy correction of varus malalignment in the knee is an unsolved issue of tremendous importance since bony corrections are applied with increasing frequency for many indications, such as unicompartmental osteoarthritis (OA), instabilities, and corrections for aesthetical reasons [ 8 , 23 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the improvement in surgical accuracy in OWHTO, there are considerable reports of a tendency toward undercorrection, and there are ongoing efforts to improve the surgical accuracy in modern OWHTO [37][38][39][40][41]. Alemayehu et al reported that the amount of compression required to fix the plate at the osteotomy site depends on the severity of the proximal tibial varus deformity.…”
Section: Preoperative Planning Using 3dmentioning
confidence: 99%